Contribución al estudio de clamidiasis felina en gatos domésticos de la ciudad de Santiago - Maier M., Liliana; González, Carlos; Court, Alfonso; García, Alex (Avances en Ciencias Veterinarias, 2001)
The presence of Chlamydiae strains as a pathogenic agent in feline conjunctivitis was studied in samples obtained from 40 cats. About 50% of the samples were positive to Chlamydia psittaci using the immunofluorescence method which seems to be an adequate technique. The most common pathogens associated with the ocular infection were Staphylococcus sp (44%), Streptococcus sp (29%) and Pseudomonas aeruginosa (10%). The zoonotic condition of Chlamydia psittaci is important as a public health matter and because of this, the cat vaccination is highly recommended.